Short Communication: Orchid diversity in the riparian area of Samin River, Central Java, Indonesia - BISMA YOGA HERDANANTA; RESSA KARINA; SOFIYANA KHOIRUNNISA; GILANG DWI NUGROHO; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Herdananta BY, Karina R, Khoirunnisa S, Nugraha GD, Setyawan AD. 2024. Short communication: Orchid diversity in the riparian area of Samin River, Central Java, Indonesia. Biodiversitas 25: 5046-5054. Riparian area provides various ecosystem services, including the habitat of orchids. This research aimed to determine the diversity of orchid species along the riverbank of Samin River, Karanganyar-Sukoharjo Districts, Central Java, Indonesia. Data collection was conducted in three segments of the river: upstream (Blumbang and Gondosuli Villages), middle stream (Girilayu and Plosorejo Villages) and downstream (Kadokan Village). At each station, explorative method using cruising path with length of 1 km along the riverbank and width of 5-10 meters on both sides was used to document the presence of orchids. Data was analyzed to produce the Shannon-Wiener biodiversity index (H'), evenness index (E), and Margalef species richness index (R). This study recorded 19 species of orchids in which 13 species with 198 individuals were found in the upstream, four species with 154 individuals in the middle stream, and two species with 2 individuals in the downstream. Orchid species with the highest frequency was Crepidium kobi. There were 5 species of terrestrial orchids and 14 species of epiphytic orchids. For the epiphytic orchid, Zone 3 on the host tree was the zone with the largest number of species and individuals found. The upstream and middle stream had moderate diversity, while the downstream had low diversity. The three stations had different evenness categories in which quite evenly distributed in the upstream, less even in the middle stream and uneven in the downstream. All three stations had low richness index. The findings of this study suggest that the importance of maintaining riparian habitats to support the sustainability of biodiversity, especially orchid. Conservation efforts can help maintain the balance of ecosystems and biodiversity in this area. This study can be the basis for more effective conservation management in riparian areas.